Dasar Hukum Tindak Pidana Penelantaran Istri Berdasarkan Undang- Undang Nomor 23 Tahun 2004 Tentang Penghapusan Kekerasan Dalam Rumah Tangga - Hasibuan, Aulia Rahman Hakim (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2023, 2023)
Today, domestic neglect of wives still occurs frequently, despite various efforts to reduce and even to overcome it. Based on this, the problem arises of what factors cause domestic neglect and how the punishment of perpetrators of domestic violence. So research is needed, namely the type of empirical legal research. In this case the law is conceptualised as an empirical symptom that can be observed and researched in the field.One form of crime that occurs in a domestic environment is domestic violence (KDRT). The thing that couples desire in a marriage is to form a family that is able to provide eternal happiness and create harmony and peace in addition to obtaining offspring in accordance with Law Number 1 of 1974 concerning Marriage. Regarding the elimination of domestic violence is regulated in Law Number 23 Year 2004